What's next: negotiating rules for a global economy - Hart, Michael (Centre for Trade Policy and Law. University of Ottawa andCarleton University OttawaCA, 1996)
Explores why a revolutionary rather than evolutionary to the World Trade Organisation and the trade agenda of the future makes sense, what such an approach would involve, the kinds of challenge that needs to be considered, the benefits that would flow from thinking big and some of the practicalities of negotiating strategies and appropriate negotiating forums that will need to be addressed.